1999
DOI: 10.1212/wnl.52.6.1201
|View full text |Cite
|
Sign up to set email alerts
|

Outer retinal dysfunction in patients treated with vigabatrin

Abstract: Article abstract-Objective: To assess early visual impairment related to vigabatrin prospectively in patients with and without visual symptoms. Background: Vigabatrin acts as an inhibitor of gamma-aminobutyric acid (GABA) transaminase. GABA-induced ion transport changes in the retinal pigment epithelium have been described. The electro-oculogram (EOG) is a clinical test that reflects photoreceptor and pigment epithelium function. Patients and methods: Of the 22 consecutive patients presenting with a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
2
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 11 publications
3
77
2
6
Order By: Relevance
“…This finding is in agreement with that of Lawden et al (8) and suggests that current VGB therapy adversely affects the Arden Index of the EOG irrespective of the field defect. It would also explain the findings of Arndt et al (5).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This finding is in agreement with that of Lawden et al (8) and suggests that current VGB therapy adversely affects the Arden Index of the EOG irrespective of the field defect. It would also explain the findings of Arndt et al (5).…”
Section: Discussionmentioning
confidence: 64%
“…Visual electrophysiology performed under nonstandardized conditions revealed reduced oscillatory potentials of the electroretinogram (ERG) in two patients, one of whom also showed an abnormally low Arden Index of the electro-oculogram (EOG). One earlier case of visual field constriction attributed to VGB therapy (2) and several other studies concerning visual field constriction attributed to VGB (3)(4)(5)(6)(7)(8)(9)(10) have been reported.…”
Section: Discussionmentioning
confidence: 96%
“…In patients who were using VGB at the time of the first examination, the EOG improved slightly. Arndt et al (1999) also found a permanent change in EOG after stopping VGB. Other researchers have claimed that the Arden ratio of the EOG is affected by current use of VGB (Bourcier Bareil et al 1999;Lawden et al 1999;Harding et al 2000;Johnson et al 2000;Coupland et al 2001;GraniewskiWijnands & van der Torren 2002).…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3][4][5][6][7][8] It is hypothesised that in addition to effects on cerebral function, irreversible inhibition of GABA aminotransferase with consequent elevation of GABA levels in the inner retina is the priniciple cause of the depressed visual function and this is supported by electrophysiological data. [9][10][11][12][13][14][15] Outer retinal and possibly also cortical effects may play a role. 12 Males may be more susceptible than females 11 but the role of other risk factors such as cumulative dosage is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Outer retinal and possibly also cortical effects may play a role. 12 Males may be more susceptible than females 11 but the role of other risk factors such as cumulative dosage is less clear. There are reports of visual recovery after drug withdrawal 16,17 but in a larger study of 13 patients, Johnson et al found no association between the recovery of visual function and either treatment duration or cumulative dosage.…”
Section: Introductionmentioning
confidence: 99%